Fundamentals of Entrepreneurship (ENT300) : Masterpiece / Mohd Nor Syaddiq Mohamad Hamsah … [et al.] - Mohamad Hamsah, Mohd Nor Syaddiq; Roslan, Dhiya Ameerul Rusyda; Aiman, Mastura; Tukiran, Nurfatin Nadiah (2012)
Our business is named MASTERPIECE which consists of four members. Each of the members contributes a certain amount of capital as agreed in the agreement. Our main business activity is selling art stationeries and also providing services which involves with arts. In Kuching area, art stationeries are really hard to find. So, our concept in opening this kind of shop really suit the area that we opened our company which is The Spring which is one of the centre of attraction in Kuching area. Our business operations start at 10 am to 9pm every day.